What shapes the support of renewable energy expansion? Public attitudes between policy goals and risk, time, and social preferences. (February 2020) - Groh, Elke D.; Möllendorff, Charlotte v.
Abstract: Climate protection goals can only be achieved if the expansion of renewable energies is publicly supported. This paper analyzes the relevance of the perceived importance of policy goals and framework conditions as well as individual risk, time, and social preferences for the support of the German energy transition. Based on data from an online survey, our empirical analysis reveals that the perceived importance of climate protection, nuclear risks, changes in the landscape and economic effects are decisive for a strong support of the energy transition. In addition, it reveals that the importance of the policy goals is driven by political orientation but also by trust and a feeling of responsibility. Therefore, this study emphasizes the need to compensate for the negative consequences of the transition process, to take confidence-building measures, and to sensitize the public for their own stake in greenhouse gas emissions. Highlights: Public support is driven by perceived policy goal importance. The feeling to be responsible for environmental protection increases support. Conservative and ecological political orientations are highly relevant. There is no evidence for an influence of risk or time preferences on support.